Challenges and opportunities for implementing open innovation from the perspective of the Brazilian legal framework for innovation - Ayroza, Igor Feitosa Lacôrte; Pedroza Filho, Manoel Xavier (Science & Technology Journals, 2024)
The objective of the present work was to identify the challenges and opportunities that emerged from the research, development, and innovation (RDI) processes of Embrapa Pesca e Aquicultura (EPA) with the implementation of open innovation (OI) based on the Brazilian legal framework for science, technology, and innovation (MLCTI). The methodology used was composed of document analysis, semi-structured interview, and content analysis, using the NVIVO software. Thirty interviews were conducted with people directly involved in the OI process of the EPA. The results indicate that, from the perspective of Embrapa employees, the OI process was motivated by the scarcity of resources, which generated a series of challenges for the company, requiring the improvement of its operation. The players of the private sector indicated the need for improvements in the OI process, to make it more agile. For the benefits arising from the OI, the optimization of partnership processes and the alignment of research with the demands of the private sector are highlighted. As benefits of the OI, the productive sector also pointed out the access to the EPA´s qualified technical team and the Embrapa’s credibility in the market.